Publisher Correction: First-principles calculation of intrinsic defect chemistry and self-doping in PbTe. (December 2017) - Goyal, Anuj; Gorai, Prashun; Toberer, Eric; Stevanović, Vladan
A correction to this article has been published and is linked from the HTML version of this article.